Efectos de la ingesta de maíz de alta calidad de proteína (QPM) versus maíz convencional en el crecimiento y la morbilidad de niños nicaragüenses desnutridos de 1 a 5 años - Ortega Aleman, EC; Coulson Romero, AJ; Ordoñez Argueta, L.I.; Pachón, Helena (2008)
Quality protein maize (QPM), with twice the amount of tryptophan and lysine than conventional maize, has improved the nutritional status of severely malnourished children. This double-blind clinical study evaluated the impact of QPM on the growth and morbidity of mild and moderately malnourished children. In a Nicaraguan day care center, 48 children 1 to 5 years old who were malnourished (> 2 indicators with <-1 Z for weight-age, height-age or weight-height) were identified and randomly assigned to consume for 5 days/week for 3.5 months a snack prepared with QPM or conventional maize. QPM positively influenced children s growth: weight (0.80 vs. 0.19 kg gained from baseline to endline between the QPM and conventional maize groups, respectively), height (2.02 vs. 1.23 cm in QPM vs. conventional) and Z score for weight-age (0.17 vs. -0.26 Z in QPM vs. conventional) and height-age (0.06 vs. -0.23 Z in QPM vs. conventional). When other factors that could affect growth with respect to weight, height, weight-age Z score and height-age Z score were controlled for, the intervention group (QPM>conventional) was a statistically important factor (P<0.01). The QPM snack, however, had no effect on the incidence of diarrheal episodes or respiratory infections. In conclusion, QPM improves the nutritional status of pre-school children who are mild or moderately malnourished but has no effect on the incidence of diarrheal episodes or respiratory infections.